2004
DOI: 10.1097/00005176-200405000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glutamine Supplementation on Diarrhea, Interleukin-8 and Secretory Immunoglobulin A in Children With Acute Diarrhea

Abstract: Duration of diarrhea was shorter in children supplemented with glutamine. The beneficial impact of glutamine supplementation seems to be through effects on gastrointestinal mucosa rather than the host immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…Alanyl-glutamine (AQ) is more stable, soluble and well tolerated and has been shown to be at least as effective as glutamine in intestinal injury repair in vitro, in vivo and in patients. [17][18][19][20][21][22][23][24] Our group has demonstrated that AQ or glutamine supplementation given to patients on HAART, decreased diarrhea rates and increased antiretroviral serum concentration, indirectly indicating improvement of the intestinal epithelial function. 21 Similarly, a clinical trial demonstrated that AQ supplementation ameliorated clinical symptoms of gastrointestinal toxicity in patients on chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Alanyl-glutamine (AQ) is more stable, soluble and well tolerated and has been shown to be at least as effective as glutamine in intestinal injury repair in vitro, in vivo and in patients. [17][18][19][20][21][22][23][24] Our group has demonstrated that AQ or glutamine supplementation given to patients on HAART, decreased diarrhea rates and increased antiretroviral serum concentration, indirectly indicating improvement of the intestinal epithelial function. 21 Similarly, a clinical trial demonstrated that AQ supplementation ameliorated clinical symptoms of gastrointestinal toxicity in patients on chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Although solutions were of similar osmolality, glucose-free Gln-based ORS did not appear to reduce stool output, volume of ORS or time required for rehydration, urine output, or vomiting. The indeterminate results of both trials could be explained by subjects being only mildly to moderately dehydrated, since ORS is more effective when given to dehydrated patients [160, 161]. Furthermore, the early feeding just after rehydration may have blunted the effects of Gln [160].…”
Section: Resultsmentioning
confidence: 99%
“…Yalçin et al [161] administered oral Gln (0.3 g/kg/d) as capsules for 7 d in 128 otherwise healthy infants aged 6 to 24 months with acute diarrhea. Compared to cornstarch placebo, Gln reduced the duration of diarrhea (Gln: 3.40 ± 1.96 d versus placebo: 4.57 ± 2.48 d, P < 0.01) for the entire cohort and among infants aged ≥12 mo, but not for infants <12 mo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutamine supplementation in rats pretreated with toxic doses of methotrexate enables reduction in the severity of the intestinal mucositis [17] and improves intestinal permeability in patients treated with 5-FU and folinic acid [18]. Although glutamine has been shown to reduce diarrhea duration in children [19][20][21] and is generally recognized to be a conditionally essential amino acid in the critically ill patient [22], there remains a debate regarding the efficacy of glutamine due to its limited solubility, stimulating the pursuit of more stable glutamine compounds for clinical use [23,24].…”
Section: Introductionmentioning
confidence: 99%